1994
DOI: 10.1111/j.2044-8260.1994.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mood on memories of parental rearing practices

Abstract: Parental rearing styles are often found to be related to adult psychological disorders. In general, conclusions are based on the data of retrospective studies, in which patients' memories of their parents' behaviour are investigated. However, it has been widely recognized that memories may be sensitive to current mood states. The possible mood sensitivity of autobiographic memories is a powerful alternative explanation of the relationship commonly found between parental rearing styles and psychopathology, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 8 publications
5
49
1
1
Order By: Relevance
“…This result is comparable to many other studies which have shown that maladaptive parental behaviours are mediating factors for children to develop depressive disorders and suicidal behaviour. [55][56][57][58][59][60][61][62][63][64][65][66][67] These maladaptive parental behaviours as documented in these previous studies were shown to form dysfunctional family settings that are associated with high rates of parent-child conflict. Comparable with results of previous studies, children raised in these environments are highly vulnerable to develop psychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is comparable to many other studies which have shown that maladaptive parental behaviours are mediating factors for children to develop depressive disorders and suicidal behaviour. [55][56][57][58][59][60][61][62][63][64][65][66][67] These maladaptive parental behaviours as documented in these previous studies were shown to form dysfunctional family settings that are associated with high rates of parent-child conflict. Comparable with results of previous studies, children raised in these environments are highly vulnerable to develop psychiatric disorders.…”
Section: Resultsmentioning
confidence: 99%
“…Comparable with results of previous studies, children raised in these environments are highly vulnerable to develop psychiatric disorders. [55][56][57][58][59][60][61][62][63][64][65][66][67] …”
Section: Resultsmentioning
confidence: 99%
“…Memories on parental rearing are not necessarily reflections of the actual behavior of the parents [3,4]. Both child and parents can have different perceptions of this parenting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Portuguese studies on its psychometric qualities show good estimators of reliability (Cronbach's Alpha of .661 and .542, for mother and father scores, respectively) and validity (confirmatory factor analysis showed that three factors explain almost half of the variance of responses). Researchers have demonstrated the high stability of reported parental rearing behaviors during significant clinical changes in the severity of psychiatric illnesses and, more specifically, of depressive disorders, excluding the hypothesis that the patients' mostly negative reports of their parents' rearing behavior were due to their depression-biased autobiographical memories (Richter and Eisemann 2000;Gerlsma et al 1994). …”
Section: Inventory For Assessing Memories Of Parental Rearing Behaviomentioning
confidence: 99%